STRENGTH ANALYSIS OF RAILWAY PASSENGER VEHICLE WATER TANK BASED ON TWO-WAY FLUID-SOLID INTERACTION - WANG LongYi; ZHAO ZeFu; LI GuoFang; DING WangCai (Jixie qiangdu)
Taking the railway passenger car water tank as the research object,the bidirectional fluid-solid coupling method is used to model and numerically analyze the liquid impact sloshing problem in the passenger car tank using the finite element analysis software ANSYS Workbench. By studying the continuous impact load on the water tanks with different water contents in the longitudinal direction of the vehicle,the change history of the tank structure stress with time and the deformation history of the tank structure with time are obtained. The results show that the maximum stress and maximum displacement of the box gradually increase with the increase of water content. Through analysis,the weak position of the box structure is determined,By plotting the comparison curve between the test value and the simulation value of each measuring point,The consistency between the calculation model of the water tank and the actual model was verified. Shows that the two-way fluid-solid coupling method and water tank model used in this paper have good reliability,which provides a reliable analysis method for the design and optimization of the water tank structure of the railway passenger car.